State Support is a Key to Increasing the Economic Efficiency of the Enterprise - Faizieva Shirin Shodmonovna (International Journal on Economics, Finance and Sustainable Development, 2022)
In the state considers the role of economic efficiency in the activities of enterprises, theoretical and methodological aspects of its development, as well as the importance of mechanisms of state support. Understands the nature and criteria of economic and social efficiency, as well as factors influencing efficiency.